Time‐resolved circularly polarized luminescence of Eu3+‐based systems. Issue 3 (30th December 2020) - Hananel, Uri; Schwartz, Gal; Paiss, Guy; Arrico, Lorenzo; Zinna, Francesco; Di Bari, Lorenzo; Cheshnovsky, Ori; Markovich, Gil
Abstract: Chiral Eu 3+ ‐based systems are frequently studied via circularly polarized luminescence spectroscopy. The emission lifetimes of each circular polarization, however, are virtually always ignored, because in a homogeneous sample of emitters, there should be no difference between the two. However, we show that in less robust Eu 3+ complex structures, as in the chiral complex Eu (facam)3, a difference in the lifetimes of the two circularly polarized emission components arises due to heterogeneity of the complexes. In this case, each species within the sample could have different degrees of circularly polarized luminescence and decay rates at certain emission lines. The superposition of the emission components of the various chiral species leads to an overall difference in decay rate between the two circular polarizations. Such a difference is also shown for Eu 3+ ‐doped chiral TbPO4 ·D2 O nanocrystals. We believe that this kind of measurement could be a unique tool for determining the homogeneity of a lanthanide‐based chiral system, where other methods might fail in this task. Abstract :